At Last! Aye, and There's the Rub. Issue 7 (3rd July 2017) - Capron, Alexander M.
Abstract : Mea culpa. In 1981 the President's Commission for the Study of Ethical Problems in Medicine and Biomedical and Behavioral Research, of which I was the Executive Director, recommended to the President and Congress that all federal departments and agencies that conduct or support human subjects research adopt "as a common core" the HHS regulations, "while permitting additions needed by any department or agency that are not inconsistent with these core provisions." The commission believed—rightly, I still think—that having uniformity would ease administration, reduce regulatory burdens, simplify oversight, and make research more efficient. Yet our naïve expectation the task could be accomplished in 180 days meant that we failed to anticipate that if it took much longer—namely, the 10 years that passed before the Common Rule was issued—federal officials would thereafter be reluctant to change the regulations and that when they tried to do so twenty years later, with the issuance of the ANPRM in 2011, they would propose comprehensive revisions. I argue that was the wrong conclusion to draw from the difficulties in issuing the first Common Rule, and that the process of producing the new "final rule" on January 19, 2017—during which many of the proposed changes were either dumped or promulgated without being adequately vetted—reinforces the conclusion that a more incremental process, with ongoing involvement of the public through an advisory body like the President's Commission, would be a much better way to proceed.